The Alburquerque Ducal Court and the Literary Patronage of Hernán López de Yanguas during Charles V’s Reign - Pacheco Landero, Diego (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2020)
This article investigates the political and cultural practices of the ducal House of Alburquerque to demonstrate its commitment to one of the basic principles of Charles V’s foreign policy, that of maintaining peace among Christians and warring against the Turk. It studies the specific conditions of the emperor’s reign that allowed the high noble courts of Castile to flourish. Among these courts, the ducal House of Alburquerque at Cuéllar is exemplary for its literary patronage of the humanist and dramatist Hernán López de Yanguas (1487–1547?), whose plays served to express the duchy’s involvement in imperial politics.